(untitled) (Andamios, Revista de Investigación Social, 2006)
This article is part of the coming book Universidad, sociedad y política. The book discusses the effects of the heterogeneous and disarticulated social context strained by an economic crisis than polarizes all the spaces that the social life have over the university. In here it is showed how in this context the university divides and discovers itself without a unified idea of its essence, as a clear sign of the modernity’s decline. From this perspective it is affirmed that the university can not be reduced to one of its roles, moreover in the contrary it should extend its social functions. In this article there are identified and criticized different projects that dispute the social and political place that the University should occupy. Particularly, there are reflections and analysis about this dispute in relation with the projects of the National Autonomous University of Mexico (UNAM).